STUDI KEMAMPUAN NIOSOM YANG MENGGUNAKAN MALTODEKSTRIN PATI GARUT (Maranta arundinaceae Linn.) SEBAGAI PEMBAWA KLORFENIRAMIN MALEA - Anwar, Effionora; Henry, Henry; Jufri, Mahdi (Makara Journal of Science, 2004)
Study of the Capability of Niosomes that Used Maltodextrin from Garut Starch (Maranta arundinaceae Linn.) as a Chlorpheniramine Maleate Carrier. The aim of this research was to study the entrapment ability of ampiphylic drug, chlorpheniramine maleate (CTM), by niosome. Like liposomes, niosomes is an encapsulated drug carrier that has important role in a drug release system. Niosomes and liposomes are unstable, but niosomes could be handled by proniosomes. Proniosomes in this research was prepared using the combination of maltodextrin DE 5-10 from arrowroot starch (Maranta arundinaceae Linn.), Span 60 and Cholesterol as non ionic surfactant in six formulas. The entrapment level of CTM depends on combination of surfactant in proniosomes, drug substance concentration and proniosomes quantity, temperature, and hydration times. Niosomes (10mM) that was prepared by proniosomes in formula 3 has been hydrated at 80 oC for 2 minutes using demineralized water could entrapped 94,04%, of 1 mM CTM. The proniosomes in formula 3 was increased up to 30 mM surfactant and 10 mM CTM in niosomes, could increase the entrapment of CTM.